Appraisal of fracture sampling methods and a new workflow to characterise heterogeneous fracture networks at outcrop. (March 2015) - Watkins, Hannah; Bond, Clare E.; Healy, Dave; Butler, Robert W.H.
Abstract: Characterising fractures at outcrop for use as analogues to fractured reservoirs can use several methods. Four important fracture data collection methods are linear scanline sampling, areal sampling, window sampling and circular scanline sampling. In regions of homogeneous fracture networks these methods are adequate to characterise fracture patterns for use as outcrop analogues, however where fractures are heterogeneous, it is more difficult to characterise fracture networks and a different approach is needed. We develop a workflow for fracture data collection in a region of heterogeneous fractures in a fold and thrust belt, which we believe has applicability to a wide variety of fracture networks in different tectonic settings. We use an augmented circular scanline method, along with areal sampling to collect a range of fracture attribute data, including orientation, length, aperture, spatial distribution and intensity. This augmented circular scanline method more than halves the time taken for data collection, provides accurate, unbiased data that is representative of local fracture network attributes and involves data collection of a wider range of fracture attributes than other sampling techniques alone. Highlights: We use field data to appraise and compare widely used fracture sampling methods. We outline a workflow combining linear and circular scan line sampling. Our workflow evaluates heterogeneous fracture networks. Our workflow compares favourably with existing sampling methods. The workflow is more efficient for evaluating fracture networks.